CUPRAC assay-guided profiling of antioxidant compounds in methanol extract of Lentinus squarrosulus Mont. mycelium - Abdullah, Sumaiyah; Abdullah, Noorlidah; Sabaratnam, Vikineswary; Yap, Ken Choy (University of Ljubljana, 2018)
A cupric reducing antioxidant capacity (CUPRAC)-guided purification approach was performed on a methanol extract of Lentinus squarrosulus (LsqMeOH) by using reversed phase-high performance liquid chromatography. Using reversed phase-high performance liquid chromatography, three fractions were separated arbitrarily named FR1, FR2 and FR3. Results showed that FR2 exhibited the highest antioxidant activity in CUPRAC assay (A450, 0.86) but not significantly different from LsqMeOH (A450, 0.84). FR1 and FR3 showed much lower absorbance, with values (A450, 0.21) and (A450, 0.36) respectively at 1 mg ml-1. The most active fraction (F3) was further subjected to LC-MS/MS to obtain its detailed chemical profile. Uridine, ganoderic acid derivative, and flavonoids were the first time being found in L. squarrosulus antioxidative fractions. The present results indicate that the fraction extracts of L. squarrosulus possess antioxidant properties and can be used as free radical inhibitors. Therefore, this research suggested the potentials of L. squarrosulus as a source of antioxidant extract to be used in food industries (functional food).